Water adsorption isotherms and thermodynamic analysis of Thai style marinated dried fish (Pla Sawan) - Chalermchat Y. (2014)
Water sorption isotherms of traditional Thai dried marinated fish (Pla Sawan) were investigated by a standard static gravimetric method. The water activity, ranging from 0.1 to 0.9, was varied using different types of saturated salt solution. The samples were placed in hermetically-sealed jars filled with saturated salt solutions and the equilibrium moisture content of the samples was determined. The experiment was conducted at temperature of 9, 26 and 50°C. Six water sorption models, namely, modified Henderson, modified Chung-Pfost, modified Oswin, modified Halsey, Brunauer-Emmet-Teller (BET) and Guggenheim-Anderson-de Boer (GAB), were fitted to the experimental data. The goodness of fit was determined using statistical criteria, i.e., coefficient of determination, root mean square error, mean relative deviation and plot of residuals. Of the models tested, GAB appeared to give the best fit to the experimental data. Monolayer water content could be estimated and compared with that estimated from BET model. It was found that the value from GAB model was higher than that from BET model. The temperature had no significant effect on the adsorption isotherms but the trend suggested that the temperature increased with decreasing moisture content. The inversion of temperature effect where the temperature positively influenced the moisture content was observed at water activity of 0.85. In addition, thermodynamic analysis was applied to gain knowledge of heat and entropy of adsorption. The best adsorption model was used to predict the equilibrium moisture contents and subsequent predicted values were used to compute thermodynamic functions, i.e., net isosteric heat of adsorption, adsorption entropy, spreading pressure and net integral enthalpy. The results showed that isosteric heat of adsorption decreased exponentially with increasing moisture content. Adsorption entropy decreased sharply with increasing moisture content. The spreading pressure increased with increasing water activity and the temperature significantly affected the spreading pressure. The integral enthalpy decreased linearly with increasing moisture content.